Law, Democracy and the Quality of Government in Africa - Simplice A. Asongu (African Governance and Development Institute (AGDI), 2011)
This paper examines the big questions of African comparative politics. It assesses the interaction of three crucial components in the development of the continent: law, democracy and quality of government. Political regimes of democracy, polity and autocracy are instrumented with income-levels, legal-origins, religious-dominations and press-freedom levels to account for government quality dynamics of corruption-control, government-effectiveness, voice and accountability, political-stability, regulation quality and rule of law. Findings indicate democracy has an edge over autocracy while the later and polity overlap. A democracy that takes into account only the voice of the majority is better in government quality than autocracy, while a democracy that takes into account the voice of the minority (polity) is worse in government quality than autocracy. As a policy implication, democracy once initiated should be accelerated to edge the appeals of authoritarian regimes and reap the benefits of time and level hypotheses.
Keywords: K00; O10; P16; P43; P50; 330; Law; Politics; Democracy; Government Policy; Development